Delayed improvement in exercise capacity after cardioversion of atrial fibrillation to sinus rhythm. Issue 5 (May 1988) - Lipkin, D P; Frenneaux, M; Stewart, R; Joshi, J; Lowe, T; McKenna, W J
Abstract : In some patients symptoms improve after the restoration of sinus rhythm from atrial fibrillation. To assess the size and mechanism of such change, exercise capacity and pulsed Doppler left ventricular inflow velocities were assessed in 20 patients with established atrial fibrillation. Treadmill exercise capacity was assessed by measuring maximal oxygen consumption and anaerobic threshold before and on day 1 and 28 days after elective DC cardioversion. The relative contribution of atrial contraction to left ventricular filling was determined by relating the maximum height of the A wave to the maximum height of the E wave (A/E) of the Doppler velocity time curve. Cardioversion was successful in 14 patients. Maximal oxygen consumption and anaerobic threshold were unchanged on day 1 and increased by day 28 in all 14 patients. The percentage improvement was inversely related to the baseline values; however, the absolute improvement was small in all patients. The mean A/E ratio increased significantly from day 1 to day 28 in all 14 patients. Thus the restoration of sinus rhythm was associated with a delayed improvement in exercise capacity that may in part be due to a slow improvement in atrial contractility and peak cardiac output after cardioversion.